Grupo interdisciplinar de terapia da mão do ambulatório de terapia ocupacional da irmandade da Santa Casa da Misericórdia de Santos: uma clínica de muitas mãos, sujeitos e reflexões - Paiva, Gisele [UNIFESP] (2015)
New theories linked to rehabilitation have come up with changes in the desing of the rehabilitation object where they propose greater emphasis on social relationships and, in a way, showing that the reductionist model is outdated. However, even though some professionals are willing to work looking the patient in its entirety, their reductionist training hampers the process. It is know that the human being experiences the groups over its development as an individual and part of a society, that health education can be favored in exchanges and group experiences and that the group approach is udes in Occupaciontal Therapy, as an important effective intervention in the acquisition of new skills, independence, care techniques and as a learning space related to the health-disease process. Thus, the objectives of this research were: To understand the changes in the daily lives of the participants of the interdisciplinar therapeutic groups of health education at the Occupational Therapy and Hand Therapy Ambulatory (OTHT) of the Irmandade da Santa Casa da Misericordia de Santos (ISCMS) [Brotherhood of the Holy House of mercy of Santos], to cognize how the groups influenced the more active participation in health care and understanding their perception regarding the creation of support network, hosting and exchange of experiences within the group. It is a retrospective and study, exploratory and qualitative, conducted with 10 participants, in which 05 had carpal tunnel syndrome and 05 had upper limb amputees, four women and men, regulars of the interdisciplinary therapeutic and health education groups taking place in OTHT Ambulatory in ISCMS. The instruments used for data collection were: semi-structured interviews; the evolution of groups and field diaries written by occupational therapy and psychology students. Data analysis was carried out following the theory of content analysis and were developed four 04 categories and thirteen 13 thematic units, respectively: treatment of occupational therapy (improvement of symptoms, guidelines and emotional aspects); group service (interaction with patients, activities, new skills and coping); greeting (conversations, confidences and mutual assistance); and the last impact on the everyday life (way of life adjustments, basic activities of daily life and social relations). As a result it was found that changes in daily life occurred in the development of greater autonomy and independence in basic activities due to reduced symptoms and through the emotional benefits as incentive, self-esteem and coping. The group influenced the more active participation in health care through a greater understanding of the health-disease process, the acquisition of new care habits and after receiving explanations and guidelines. The participants perceived the group as a space to share and learn from each other and felt welcomed by the conversations and confidences. The support networks, through interpersonal relations, have strengthened considerably inside the group, but did not expand beyond this. Final thoughts: a group intervention influenced satisfactorily in routine changes and the personal life of the participants, thus being considered a powerful resource for working with this population.